ANALISIS SEKTOR UNGGULAN TERHADAP PENYERAPAN TENAGA KERJA - Nisa', Khoirun; Ajeng Kartika Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Gerbangkertosusila is a development area that contributes the largest income in East Java. However, the high Gross Regional Domestic Product (GRDP) in this region is apparently followed by a high unemployment rate. Therefore, it is necessary to identify and develop leading sectors that have the potential to absorb a lot of labor. This study aims to analyze the influence of each leading sector on labor absorption in the Gerbangkertosusila region from 2013 to 2022. The sectors analyzed include the manufacturing industry sector, construction sector, trade and repair sector, accommodation and food beverage supply sector, also information and communication sector. The results of the analysis show that the manufacturing industry sector and the trade and repair sector are effective in absorbing a lot of labor. Meanwhile, the construction sector, accommodation and food beverage supply sector, and information and communication sector are less effective in absorbing labor. The two sectors that are effective in absorbing a lot of labor should be the main focus of regional development in order to increase regional economic growth, increase community income, and reduce the unemployment rate.